The Development of a Locally-Based Virtual Gallery Grounded in Folklore Wisdom for Enhancing Creative Thinking Skills at Sekolah Alam - Ibnu Hajar; Sri Milfayetty; Ulfa Annida Damanik (STAI Hubbulwathan Duri, 2023)
This study focuses on the development of a virtual gallery media based on local wisdom of folktales, aiming to improve creative thinking abilities in Sekolah Alam. The utilization of technology in educational settings has become increasingly important in fostering innovative and engaging learning experiences. By incorporating local folklore into a virtual gallery, students can explore and appreciate their cultural heritage while enhancing their creative thinking skills. This research employed a mixed-method approach, combining qualitative and quantitative data collection methods. The results indicate that the implementation of the virtual gallery positively influenced students' creative thinking abilities, as evidenced by their improved problem-solving skills, originality of ideas, and flexibility in thinking. The findings suggest that integrating local wisdom through virtual galleries offers a promising avenue for promoting creative thinking in educational environments, particularly within the context of Sekolah Alam. Further studies could explore the long-term effects of this approach and investigate other potential benefits that may arise from incorporating local wisdom into technology-enhanced learning platforms.